Environmental-friendly Eco-labeling Matters: Evidences From an ERPs Study - Jin, Jia; Dou, Xiaodong; Meng, Liang; Yu, Haihong (Frontiers in Human Neuroscience, 2018)
Nowadays, the international community is becoming increasingly concerned about the sustainable utilization of natural resources. In order to protect the environment and reward sustainable practices, eco-labeling that signifies the environmental friendliness of the labeled food is already widely promoted in many regions around the world. Thus, it is of great importance for researchers to study consumers’ attitudes toward eco-labeled food as food is supposed to satisfy consumers’ needs. This study employed the event-related potentials (ERPs) approach to investigate consumers’ attitudes toward eco-labeled food by comparing their neural processing of visual stimuli depicting eco-labeled and non-labeled food. Our results showed that behaviorally, participants preferred to buy eco-labeled food rather than non-labeled one. At the neural level, we observed markedly smaller P2 and N2 amplitudes when pictures of eco-labeled food were presented. Furthermore, we also found that amplitudes of P2 were negatively correlated with participants’ purchase intention. Therefore, our current findings suggest that, while the environmental-friendly eco-labeling was not to one’s own interests, it might still be evocative, which induce consumers’ positive emotion, bring less cognitive conflict to the purchase decision-making and then result in a greater purchasing intention. This effect might be the result of the delivered value of social desirability.